Hurel 2023. Tales, Fables and Narratives of Rwanda - Schmidt, Sigrid (AAeO - Afrikanistik-Aegyptologie-Online, 2024)
Eugène Hurel. Tales, Fables and Narratives of Rwanda. Imiganí y’ú Rwaanda, transcribed in the scientific notation for Kinyarwanda and translated into English and German by Matthias Brack, Leo Sibomana and John Doldo IV. Rüdiger Köppe Verlag, Köln. ISBN 978-3-89645-743-1, 49,80 €. New revised edition of the collection La poésie chez les primitifs ou Contes, fables, récits et proverbes du Rwanda (Lac Kivu) by the Belgian missionary Eugène Hurel, originally published in 1922.